2020
DOI: 10.3390/vehicles2040034
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Vehicle Body Elements and Rear Axle Elements for Describing Road Booming Noise

Abstract: For investigating influences of vehicle components on the acoustic comfort at low frequencies, e.g., the booming noise behavior of a vehicle, building a whole car simulation model is useful. To reduce the model’s complexity and to save resources in the validation process, we first identify relevant components before building the model. Based on previous studies, we focus on the vehicle’s body and the rear axle. In this paper, we analyze which axle and body elements are crucial for describing road booming noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Since only the transfer paths of the rear axle (excluding the rear springs) are relevant for the description of road booming noise [8], only the six marked connection points of the chassis to the body are used. There are three directions per point, i.e., 18 internal forces.…”
Section: Chassis and Powertrain Simulation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Since only the transfer paths of the rear axle (excluding the rear springs) are relevant for the description of road booming noise [8], only the six marked connection points of the chassis to the body are used. There are three directions per point, i.e., 18 internal forces.…”
Section: Chassis and Powertrain Simulation Modelmentioning
confidence: 99%
“…We focus on the road booming noise, which is mainly excited by non-uniform road profiles [4,5]. The excitation introduced into the chassis primarily causes the rear axle to resonate in a pitching and lifting motion [6][7][8]. The vehicle's body responds with a coupled vibration mode formed by the first bending mode of the body, a rigid-body motion of the tailgate and the first longitudinal mode of the air cavity [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selvaraj et al [2] analyzed low-frequency noise and vibration problems in bus bodies, which stem from imbalances in large bus propeller shafts, using the operational deflection shape (ODS) technique. Herrmann et al [3] investigated the mechanisms behind the booming noise generated by coupling modes between the rear axle and vehicle body, which subsequently affect the fore-aft behavior of tailgates and the acoustics within the vehicle interior. Lim et al [4] identified the origins of structure-borne and airborne booming noise originating from the rigid modes of air-conditioning pipes through transmission path analysis and ODS analysis.…”
Section: Introductionmentioning
confidence: 99%